Comparing Geometric Parameters of the Cavitation Reactor In Removing Persistent Compounds from Surface Water (Latakia University Journal -Engineering Sciences Series, 2024)
The problem of contamination of drinking water sources with polycyclic aromatic hydrocarbons (PAHs) has become a global issue that must be addressed, due to their toxic carcinogenic effects. This research aims to remove (PAHs) from the water of Sureat Lake in Banias, using an effective hydrodynamic cavitation treatment technique by applying two different types of orifice plates (Plate No. 1 and Plate No. 2) used as a cavitation device in a hydrodynamic cavitation reactor to improve the efficiency of removing (PAHs). The effect of four different parameters such as hydraulic properties (flow rates, hole velocities, and cavitation number at different inlet pressures), comparison of inlet pressure (1-9 bar) and operating time (0 to 30 min) in terms of removal of (PAHs) were studied.The results obtained confirmed that plate 2, with a configuration of holes with a diameter of 1.5 mm and 17 holes, performed better with 100% complete removal of (PAHs) at a pressure of 5 bar and an operating time of 25 min compared to plate 1, which contains one hole with a diameter of 2 mm, with a removal of 100 % of aromatic compounds at a pressure of 7 bar and a time of 30 min. From this, it was concluded that plate No. 2 was the best economically and environmentally friendly for removing (PAHs) from the water of Sureat Lake, which contributes to securing water suitable for human use.